Pilot and feasibility studies: extending the conceptual framework - Bond, C; Lancaster, GA; Campbell, M; Chan, C; Eddy, S; Hopewell, S; Mellor, K; Thabane, L; Eldridge, S (BioMed Central, 2023)
In 2016, we published a conceptual framework outlining the conclusions of our work in defining pilot and feasibility studies. Since then, the CONSORT extension to randomised pilot and feasibility trials has been published and there have been further developments in the pilot study landscape. In this paper, we revisit and extend our framework to incorporate the various feasibility pathways open to researchers, which include internal pilot studies. We consider, with examples, when different approaches to feasibility and pilot studies are more effective and efficient, taking into account the pragmatic decisions that may need to be made. The ethical issues involved in pilot studies are discussed. We end with a consideration of the funders’ perspective in making difficult resource decisions to include feasibility work and the policy implications of these; throughout, we provide examples of the uncertainties and compromises that researchers have to navigate to make progress in the most efficient way.